2004
DOI: 10.1007/s00383-004-1261-0
|View full text |Cite
|
Sign up to set email alerts
|

Botryoid Wilms? tumor: a report of two cases

Abstract: We report two rare cases of botryoid Wilms' tumor (BWT) occupying the renal collecting system with no macroscopic parenchymal mass. In case 1, a 3-year-old boy presented with a mass in the right flank, low-grade fever, abdominal pain, and macrohematuria. Radiology revealed an enlarged right kidney with a heterogeneous mass occupying a large part of the dilated renal calyx, pelvis, and ureter. Radical right nephroureterectomy was performed. The histopathologic diagnosis was nephroblastoma, and the pedicle of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…[1,2] In our two cases, the renal parenchyma was shown around the masses by CT. The border between the lesion and the renal parenchyma was not clear on the unenhanced scan, but it was obvious on the enhanced scan.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…[1,2] In our two cases, the renal parenchyma was shown around the masses by CT. The border between the lesion and the renal parenchyma was not clear on the unenhanced scan, but it was obvious on the enhanced scan.…”
Section: Discussionmentioning
confidence: 87%
“…The mass shows no or slight enhancement on the contrasted scan. [1][2][3][4] The density of the lesion was similar to that of the renal parenchyma (CT value approximately 16-29 HU). Enhanced CT revealed that the lesion presented with mild or moderate enhancement (41-67 HU).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations